2004
DOI: 10.1097/00019052-200402000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic optic neuropathies

Abstract: Application of the studies described in this paper should allow the clinician to more accurately diagnose ischemic optic neuropathies and counsel the patient with regard to appropriate management, prognosis for visual recovery and future risk of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
83
0
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(91 citation statements)
references
References 66 publications
1
83
0
7
Order By: Relevance
“…In addition, because poor visual outcome does not necessarily rule out the diagnosis of IDON After LHON, ischemic optic neuropathy (ION) is the second commonest disorder mimicking optic neuropathy in our group. There are many overlapping clinical features between ION and ON and in some patients it can be very difficult to distinguish between these two diagonoses 21,22 . Some researchers have suggested that there is an overlap of the mechanism of pathogenesis, making it difficult to distinguish with certainty between an "inflammatory" and "ischemic" etiology of optic neuropathy in certain caese 23 .…”
mentioning
confidence: 99%
“…In addition, because poor visual outcome does not necessarily rule out the diagnosis of IDON After LHON, ischemic optic neuropathy (ION) is the second commonest disorder mimicking optic neuropathy in our group. There are many overlapping clinical features between ION and ON and in some patients it can be very difficult to distinguish between these two diagonoses 21,22 . Some researchers have suggested that there is an overlap of the mechanism of pathogenesis, making it difficult to distinguish with certainty between an "inflammatory" and "ischemic" etiology of optic neuropathy in certain caese 23 .…”
mentioning
confidence: 99%
“…Дополнительными аргументами в пользу того, что на-рушение гемодинамики в сетчатке и других структурах зри-тельной системы является ведущей причиной снижения зрительных функций, являются описанные многими авто-рами снижение СОЗ различной степени, снижение кон-трастной чувствительности, ограничения и дефекты полей зрения при острой и хронической ИОН [4,35], сахарном диабете [36], глаукоме [37] и других заболеваниях [38][39][40][41][42].…”
Section: результаты и обсуждениеunclassified
“…14 The nonarteritic variant (NAION) has an annual incidence of 2.3-10.2 per 100 000 adults aged over 50 years in the United States. 15,16 It typically produces a rapid onset of painless monocular visual loss that worsens over hours to days, with associated optic disk edema that can be hyperemic (Figure 1c) or pallid, 17 and a relative afferent pupillary defect.…”
Section: Nonarteritic Anterior Ischemic Optic Neuropathymentioning
confidence: 99%
“…14 In a multicenter randomized trial, optic nerve sheath decompression was found to be ineffective and possibly harmful. 24 Although there is no proven prophylactic therapy to prevent NAION, most authors advocate control of vascular risk factors and the use of antiplatelet therapy, as there is about a 15% chance of recurrence in the fellow eye in the first 5 years following the initial presentation.…”
Section: Nonarteritic Anterior Ischemic Optic Neuropathymentioning
confidence: 99%
See 1 more Smart Citation